Nanoemulsion Preparation, Identification and Evaluation Review - Mustafa R. Abdulbaqi (Journal of Global Pharma Technology, 2016)
Nanoemulsions consist of two immiscible liquids combined with emulsifying agents (surfactants and co-surfactants) in a thermodynamically stable, colloidal dispersion system, in order to form the same phase. Nanoemulsions have been thoroughly investigated as drug delivery systems. This review is aimed at providing comprehensive information on various techniques of nanoemulsion preparation and identification. There are two different methods for formulating nanoemulsions, the method of persuasion and the method of brute force. Different identification techniques for nanoemulsions include determination of trap efficiency, particle size, polydispersity index, zeta potential as well as characterization by differential scanning calorimetry, Fourier-transform infrared spectroscopy and transmission electron microscopy. Nanoemulsions are further assessed by studying in vitro release of drugs, in vitro permeation, stability and thermodynamic stability, shelf life, dispersibility, viscosity, surface tension, refractive index, percentage of transmittance, pH and osmolarity.Key words: Nanoemulsions, Nanoemulsion preparation, Identification techniques